1996
DOI: 10.1021/bi952217p
|View full text |Cite
|
Sign up to set email alerts
|

Fast Events in Protein Folding:  Helix Melting and Formation in a Small Peptide

Abstract: The helix is a common secondary structural motif found in proteins, and the mechanism of helix-coil interconversion is key to understanding the protein-folding problem. We report the observation of the fast kinetics (nanosecond to millisecond) of helix melting in a small 21-residue alanine-based peptide. The unfolding reaction is initiated using a laser-induced temperature jump and probed using time-resolved infrared spectroscopy. The model peptide exhibits fast unfolding kinetics with a time constant of 160 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

88
756
5
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(851 citation statements)
references
References 44 publications
88
756
5
2
Order By: Relevance
“…15,16,18,21,22,[28][29][30][31] Experimentally, rapid laser-induced T-jump methods have allowed the first investigations of the formation of -helices. [4][5][6][7][8][9][10][11] In these studies, a rapid T-jump pulse induces a shift in the equilibrium between the coil and helix states, and the subsequent relaxation toward the new thermal equilibrium point is probed by examining all of the amide groups via either IR 4,8,11 or Raman 7 spectroscopy, or individual residues by fluorescence spectroscopy 5 or isotopeediting 9,10 techniques. However, the peptides used in these studies are rather similar.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,18,21,22,[28][29][30][31] Experimentally, rapid laser-induced T-jump methods have allowed the first investigations of the formation of -helices. [4][5][6][7][8][9][10][11] In these studies, a rapid T-jump pulse induces a shift in the equilibrium between the coil and helix states, and the subsequent relaxation toward the new thermal equilibrium point is probed by examining all of the amide groups via either IR 4,8,11 or Raman 7 spectroscopy, or individual residues by fluorescence spectroscopy 5 or isotopeediting 9,10 techniques. However, the peptides used in these studies are rather similar.…”
Section: Introductionmentioning
confidence: 99%
“…To date, synthetic schemes have been successfully developed for the synthesis of R-helix-forming peptides, and much has been uncovered about their folding dynamics (6)(7)(8)(9)(10)(11)(12)(13). In contrast, only limited progress has been made toward understanding the synthesis of and the dynamics of -sheet peptides.…”
mentioning
confidence: 99%
“…F s forms an α-helix and was studied using circular dichroism (CD) as well as infrared (IR) spectroscopy. The melting temperature measured by IR was 334 K [18], whereas the CD-based studies obtained T m = 308 K [17] and T m = 303 K [19]. Computational studies of F s were also reported [20][21][22].…”
Section: Foldingmentioning
confidence: 99%